Evaluasi Manajemen Sumber Daya Teknologi Informasi Menggunakan Kerangka Kerja COBIT 5 Dengan Domain EDM04, APO07 dan DSS03 Pada Biro Teknologi Informasi Yayasan Bina Sarana Informatika - Glady Putra Pratama; Yusi Tyroni Mursityo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Bina Sarana Informatika Foundation is a private education institution based in Jakarta. Bina Sarana Informatika Foundation operates 48 universities in 19 major capitals in Indonesia. The company's IT resource management is delegated to the Information Technology Bureau which is responsible for managing and managing all IT assets and for developing the information systems needed by the company. Based on the results of observations and interviews conducted, found several problems that often occur related to information systems technology (IT) organizations. The types of problems that often arise among others are hampered the handling process Problems caused by human resource planning in the Information Technology Bureau are not running well, making it easier for employees to do the work to be inappropriate. Therefore, an evaluation that uses suitable work is needed to be given assistance in the field of information technology (IT). COBIT 5 supports this research on COBIT because COBIT 5 has a research process related to this study. This second process is EDM04 (Ensure Resource Optimization) as the main domain of resource management technology information and APO07 (Managing Human Resources) as a process of managing human resources. To synergize this Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer 2 Fakultas Ilmu Komputer, Universitas Brawijaya second process, DSS03 domain (Manage Problems) choose the desired process. This study aims to obtain the value of capability (capability level) and gap value (gap level) to obtain solutions and evaluations related to existing problems. From the results of the assessment carried out, it was found that the capability of EDM04 and APO07 sub domains depends on level 1 (Performed Process) with the desired target level of 2 and DSS03 sub-level at level 2 (Managed Process) with the desired target level is 3. First Results, the following are 1. The recommendations given are given to the main license and personnel functions, a personnel approval planning process is held, and documents to deal with problems related to the process until the review process.